(untitled) (Italian Journal of Public Health, 2008)
Background: The European Commission funds a European research project titled “Health Risk from Environmental Pollution Levels in Urban Systems” (HEREPLUS) that focuses on environmental health within Europe. The HEREPLUS project was presented at the 16th EUPHA conference in Lisbon in November 2008 within a workshop named “The assessment of the effect of air pollution on population and environmental health: the integration of epidemiology and geographical information system (GIS)”. Methods: The HEREPLUS project aims to measure the correlation between air pollution (especially ozone and particulate matter), meteorology, vegetation and human health in four European cities (Rome, Madrid, Athens and Dresden) by using a Geoinformation System to develop risk maps and subsequently guidelines to reduce air pollution and number of diseases. Results: The project started in September 2008 and a large, structured, relational database has been developed and completed. A literature review including national as well as international scientific literature goes on and will be completed in April 2009. Final results will be presented and published in 2011. Conclusions: Detailed scientific knowledge is important and needed to implement environmental programmes with the overall aim to protect human population against environmental related diseases.